Unpaid Household Work: A Site of Learning for Women with Disabilities - Matthews, Ann (University of Toronto, Ontario Institute for Studies in Education, 2011)
This thesis explores women's learning in unpaid household work through the lenses of impairment and disability. Informal learning from this standpoint is a perspective that is not yet integrated into the adult learning literature. The impetus for the study came from dissatisfaction with the social undervaluing of unpaid housework and carework, and the largely unrecognized learning behind the work, which is predominantly done by women. Disability and impairment provide unique lenses for making visible what people learn and how they learn in this context. Those who have or acquire impairment in adulthood need to learn how to do things differently. For this study I have taken a segment of data from a 4-year, 4-phase project on Unpaid Housework and Lifelong Learning in which I participated. The participants in this segment are women and men with disabilities who took part in 2 focus groups (11 women), an on-line focus group (20 women), and individual interviews (10 women and 5 men). Learning is explored through three different themes: first, learning related to self-care; second, learning to accept the impaired body; and third, strategies and resources used in the learning process. Analysis of the data shows that the learning that happens through unpaid household work is multidimensional, fluid, and diverse. Learning is accomplished through a complex 4-dimensional process involving a blend of the body, mind, emotions, and the spiritual self. Furthermore, what participants learned and how they learned is influenced by the sociocultural context in which it takes place. Learning, when seen as a 4-dimensional process, provides a framework for challenging traditional Western cultural beliefs about what counts as learning and knowledge. Such beliefs have cultivated the viewpoint that learning is individualistic, cognitive, and based on reason. I contest these beliefs by disrupting the binaries that support them (e.g., mind vs. body, reason vs. emotion). Participants used both sides of the binaries in their learning processes, negating the oppositional and hierarchical categories they establish. The concepts in the binaries still exist but the relationship between them is not oppositional, nor is one concept privileged over another, either within or across binaries.